(untitled) (Ibrahim Cardiac Medical Journal, 2017)
Objective: The present study was undertaken to determine the risk factors for Gestational Diabetes Mellitus (GDM) presented at Bangladesh Institute of Research in Diabetes, Endocrine & Metabolic Disorders (BIRDEM). Materials & methods: The present case-control study was conducted at BIRDEM Hospital, Dhaka over a period of 6 months from July to December 2011. A total of 100 pregnant women (20 cases and 80 controls) were consecutively enrolled in the study. Pregnant women who developed diabetes at their 3rd trimester were cases (n = 20), while pregnant women free from diabetes at their 3rd trimester were controls (n = 80). The diagnosis of GDM was made using a two-step approach. Pregnant women were initially screened by measuring the plasma glucose concentrations 1 hour after a 50 gram of oral glucose challenge. A diagnostic oral glucose tolerance test was performed on the subset of women whose plasma glucose concentrations exceded the threshold value for glucose (> 140 mg/dl). Result: The study showed that older patients (≥ 25 years) were predominant in both case and control groups. The groups were almost comparable in terms of socioeconomic status and occupation. The distribution of gestational age was also similar between groups (33.1 ± 6.3 vs. 34.2 ± 3.9 years, p = 0.476). Majority (85%) of the cases had family history of diabetes (p < 0.001). Thirty five percent of cases were nulipara and 65% multipara compared to 51.3% and 48.7% respectively of the control (p = 0.076). No significant difference was observed between the groups in terms of preterm labour and PROM (p = 0.690 and 0.220 respectively). Forty percent of cases had past history of GDM compared to 3.8% of controls (p < 0.001). The fasting plasma glucose and plasma glucose 2 hrs after 75 g of glucose ingestion were significantly higher in pregnant women having GDM than those in normal pregnant women (8.3 ± 3.1 vs. 4.1 ± 0.5 mmol/L, p < 0.001;12.9 ± 4.8 vs. 5.9 ± 1.2 mmol/L, p < 0.001 respectively). Conclusion: The study concluded that none of the sociodemographic characteristics like age, socioeconomic status and occupation was found to be associated with GDM. However, pregnant women with family history of diabetes are at risk of developing GDM significantly more than those without GDM. Multipara tend to develop GDM more frequently than the primipara does. Past incidence of GDM increases the risk of GDM in the subsequent pregnancy. Ibrahim Card Med J 2015; 5 (1&2): 49-53